Quantitative Assessment of a Financial System-Barbados. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
A banking system module is incorporated into the Central Bank of Barbados's multisectoral macroeconomic forecasting model, and a medium-term forecast is generated for bank capitalization, profitability, liquidity and nonperforming loans. Stress tests are performed for the first year of the forecast, to test the banking system's resilience to real sector shocks. The analysis, which would in practice be only part of the vulnerability assessment, indicates that the banking system is stable and resilient to macroeconomic shocks of a type and magnitude that Barbados has experienced in the past.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet